Self-care knowledge in patients with intestinal stomas in a selected hospital in the south of Viet Nam: A descriptive cross-sectional study - Thi Dung Ngo; Miranda Hawks; Thi Thanh Truc Nguyen; Thi Ngoc Han Nguyen; Hong Thiep Nguyen; Nguyen Thanh Truc Mai (Belitung Nursing Journal, 2023)
Background: Intestinal stomas are surgical interventions that have an impact on both physical and psychological health, necessitating patient self-care. Insufficient knowledge regarding peristomal skin care, prevention, and treatment of potential problems can lead to an increase in stoma-related complications. Objective: This study aimed to assess patients’ knowledge of self-care for intestinal stomas and examine the relationship between background information and self-care knowledge. Methods: A descriptive cross-sectional study was conducted from December 2021 to December 2022 at the Can Tho University of Medicine and Pharmacy Hospital in Vietnam, involving 74 participants with intestinal stomas. A questionnaire consisting of 24 closed-ended questions was used to evaluate participants' knowledge of self-care for intestinal stomas. Descriptive statistics, Chi-square, and Fisher’s exact tests were employed for data analysis. Results: The findings revealed that 54.1% of participants had good knowledge of general self-care for intestinal stomas. The distribution of good knowledge among participants was as follows: basic knowledge (66.2%), self-care practice (56.8%), recognizing and managing complications (31.1%), and dietary knowledge (64.8%). Significant relationships were observed between participants’ self-care knowledge and their education level (p = 0.002), marital status (p = 0.017), nurses’ education (p = 0.021), and hospitalization (p = 0.001). Conclusion: The proportion of participants with good knowledge of self-care for intestinal stomas was relatively low, and it was associated with individuals' education level, marital status, nurses’ education, and hospitalization. This study highlights the need for ongoing development of educational programs on self-care for intestinal stomas. These programs should be tailored to address the specific needs of each patient and aim to improve their self-care knowledge in a meaningful and sustainable manner. By investing in patient education, healthcare professionals, particularly nurses, can assist individuals with intestinal stomas in achieving better outcomes and preventing potential complications.